A Novel Hybrid Piezoelectric-Electromagnetic Micro-Power Generator by Harvesting Low Frequency Acoustic Energy. Issue 1 (December 2020) - Chen, Yuansheng; Gu, Cong; Chen, Wei; Zhao, Pengcheng
Abstract: In order to harvest low frequency acoustic energy, a novel hybrid piezoelectric-electromagnetic micro-power generator was developed with Helmholtz resonator, piezoelectric patch, coil and permanent magnet. When the sound waves enter Helmholtz resonator, piezoelectric patch and coil will be vibrated then the electric energy are generated from them. With Multisim software, the circuit of proposed micro-power generator was simulated and its output performance was analysed. Results show that there is always an optimal resistance to maximize the output power of the novel hybrid piezoelectric-electromagnetic micro-power generator. Especially when the sound waves at 82Hz, the output power of proposed hybrid generator can more than the sum of independent piezoelectric and electromagnetic micro-generator. It indicates the power generation efficiency is significant significantly improved by the proposed hybrid method.